Mutual Modulation Between Extracellular Vesicles and Mechanoenvironment in Bone Tumors - Urciuoli, Enrica; Peruzzi, Barbara (Frontiers in Cell and Developmental Biology, 2021)
The bone microenvironment homeostasis is guaranteed by the balanced and fine regulated bone matrix remodeling process. This equilibrium can be disrupted by cancer cells developed in the bone (primary bone cancers) or deriving from other tissues (bone metastatic lesions), through a mechanism by which they interfere with bone cells activities and alter the microenvironment both biochemically and mechanically. Among the factors secreted by cancer cells and by cancer-conditioned bone cells, extracellular vesicles (EVs) are described to exert pivotal roles in the establishment and the progression of bone cancers, by conveying tumorigenic signals targeting and transforming normal cells. Doing this, EVs are also responsible in modulating the production of proteins involved in regulating matrix stiffness and/or mechanotransduction process, thereby altering the bone mechanoenvironment. In turn, bone and cancer cells respond to deregulated matrix stiffness by modifying EV production and content, fueling the vicious cycle established in tumors. Here, we summarized the relationship between EVs and the mechanoenvironment during tumoral progression, with the final aim to provide some innovative perspectives in counteracting bone cancers.